Modulation of Signaling Mediated by TSLP and IL-7 in Inflammation, Autoimmune Diseases, and Cancer - Marković, Iva; Savvides, Savvas N. (Frontiers in Immunology, 2020)
Thymic Stromal Lymphopoietin (TSLP) and Interleukin-7 (IL-7) are widely studied cytokines within distinct branches of immunology. On one hand, TSLP is crucially important for mediating type 2 immunity at barrier surfaces and has been linked to widespread allergic and inflammatory diseases of the airways, skin, and gut. On the other hand, IL-7 operates at the foundations of T-cell and innate lymphoid cell (ILC) development and homeostasis and has been associated with cancer. Yet, TSLP and IL-7 are united by key commonalities in their structure and the structural basis of the receptor assemblies they mediate to initiate cellular signaling, in particular their cross-utilization of IL-7R. As therapeutic targeting of TSLP and IL-7 via diverse approaches is reaching advanced stages and in light of the plethora of mechanistic and structural data on receptor signaling mediated by the two cytokines, the time is ripe to provide integrated views of such knowledge. Here, we first discuss the major pathophysiological roles of TSLP and IL-7 in autoimmune diseases, inflammation, and cancer and subsequently curate structural and mechanistic knowledge about receptor assemblies mediated by the two cytokines. Finally, we review therapeutic avenues targeting TSLP and IL-7 signaling. We envision that such an integrated view of the mechanism, structure, and modulation of signaling assemblies mediated by TSLP and IL-7 will enhance and fine-tune the development of more effective and selective approaches to further interrogate the role of TSLP and IL-7 in physiology and disease.